An Analysis of the Psychosocial Impact of Unreported and Late-Reported Sexual Crimes on Victims in Indonesia - Sudarno Sudarno; Nemos Muhadar; Rahel Stevani Sulo; Mauren Cristina Lasmono (UNISSULA, 2026)
This study examines the psychosocial impact of unreported and late-reported sexual crimes and their implications for victims’ recovery and rehabilitation in Indonesia. Delayed reporting intensifies psychological harm and contributes to long-term conditions that hinder individual functioning and social reintegration. Employing an empirical juridical approach through a systematic literature review and in-depth interviews with law enforcement officials, this study finds that delayed reporting exacerbates trauma manifestations, including post-traumatic stress disorder, depression, and anxiety, while reinforcing social withdrawal. Data from the South Sulawesi Regional Police indicate that approximately 99% of reported sexual violence cases were reported late, demonstrating a strong associatFion between delayed reporting and prolonged rehabilitation. Furthermore, Makassar City Police data (January–August 2024) show that only 2.2% of reported cases reached the prosecution stage (P21), while 32.6% were terminated (SP3) due to evidentiary constraints commonly associated with late reporting. The enactment of Law Number 12 of 2022 on Sexual Violence Crimes represents a significant advancement through its victim-centered approach, expanded definitions of sexual violence, and recognition of alternative forms of evidence. Nevertheless, its effectiveness remains limited by evidentiary challenges and socio-cultural barriers, particularly the Siri’ norm. This study concludes that the success of the UU TPKS depends on integrated institutional implementation and broader cultural transformation.